Taxing the cloud: introducing a new taxation system on data collection? - Primavera De Filippi (Internet Policy Review, 2013)
Cloud computing services are increasingly hosted on international servers and distributed amongst multiple data centres. Given their global scope, it is often easier for large multinational corporations to effectively circumvent old taxation schemes designed around the concept of territorial jurisdiction and geographical settings. In view of obtaining tax revenues from these online operators whose business is partially carried out in France, the French government recently issued a report emphasising the need for new taxation rules that would better comply with the way value is generated in the digital economy: at the international level, it is suggested that taxation should be calculated according to the place of interaction with end-users; at the national level, the report suggests to introduce a transitory tax on data collection in order to promote innovation and encourage good online practices.
Keywords: 300; Taxing; Cloud services; Apple; Google; Amazon; Facebook; Twitter; France; Cloud; Cloud computing; Taxation; Fiscality; Data protection; Data collection